ANALISIS SISTEM INFORMASI AKUNTANSI DALAM PENYUSUNAN PELAPORAN KEUANGAN DINAS SOSIAL PEMBERDAYAAN EREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Maya Tri Hastuti; Diana Sari Wijayanti, Irine (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
ABSTRACT Dinsos P3A of Gunungkidul Regency, Special Region of Yogyakarta, plays a crucial role in the implementation of social welfare programs, particularly in women's empowerment, child protection, and poverty alleviation. Accurate and transparent financial reporting is key to ensuring program accountability and effectiveness. This study aims to analyze the implementation of an Accounting Information System (AIS) in the preparation of financial reports at the Social Service for Women's Empowerment and Child Protection (Dinsos P3A) of Gunungkidul Regency. The method used was qualitative analysis using the Miles and Huberman model, which encompasses data collection, reduction, verification, and conclusion. The results indicate that the AIS has improved efficiency, accuracy, and transparency in financial report preparation. However, there are challenges in technical understanding and IT infrastructure. Factors contributing to the success of AIS implementation include staff training and management support. Solutions to address these challenges include increased training, infrastructure improvements, and strengthening the monitoring and evaluation system. Optimal implementation of the AIS is expected to improve the quality of financial reporting at the Social Service for Women's Empowerment and Child Protection (Dinsos P3A) of Gunungkidul Regency.